Utilizing the ChatGPT: An Innovative Method for Simulating Patient Conversations in Community Pharmacy Settings - Phetmanee, Thidarat; Phetmanee, Surasak (Interprofessional Journal of Health Sciences, 2023)
Generative AI, notably ChatGPT by OpenAI, is making waves in the educational sphere, opening new, innovative avenues to deepen and enhance student learning experiences. ChatGPT shows promising capabilities as an educational resource, particularly in health science and healthcare management. The report was to illustrate prompts to AI chatbots can create realistic simulations of patient interactions in community pharmacy environments, providing essential feedback for learners in the process. Simulations were organized into four categories: simulated patients with common or specific diseases, each further divided with and without a designated Drug-Related Problem (DRP). Findings reveal ChatGPT's ability to mimic a genuine patient, providing detailed and contextually relevant responses. It delivered a unique, authentic learning interaction, diverging from traditional laboratory practices and providing essential feedback to learners. In conclusion, ChatGPT proves to be a powerful simulated patient tool in community pharmacy practice, acting as an effective learning platform where pharmacy educators can help students polish their dispensing skills.